Two Cell Adhesion Molecules, Nectin and Cadherin, Interact through Their Cytoplasmic Domain–Associated Proteins - Tachibana, Kouichi (The Rockefeller University Press, 2000)
We have found a new cell–cell adhesion system at cadherin-based cell–cell adherens junctions (AJs) consisting of at least nectin and l-afadin. Nectin is a Ca(2+)-independent homophilic immunoglobulin-like adhesion molecule, and l-afadin is an actin filament-binding protein that connects the cytoplasmic region of nectin to the actin cytoskeleton. Both the trans-interaction of nectin and the interaction of nectin with l-afadin are necessary for their colocalization with E-cadherin and catenins at AJs. Here, we examined the mechanism of interaction between these two cell–cell adhesion systems at AJs by the use of α-catenin–deficient F9 cell lines and cadherin-deficient L cell lines stably expressing their various components. We showed here that nectin and E-cadherin were colocalized through l-afadin and the COOH-terminal half of α-catenin at AJs. Nectin trans-interacted independently of E-cadherin, and the complex of E-cadherin and α- and β-catenins was recruited to nectin-based cell–cell adhesion sites through l-afadin without the trans-interaction of E-cadherin. Our results indicate that nectin and cadherin interact through their cytoplasmic domain–associated proteins and suggest that these two cell–cell adhesion systems cooperatively organize cell–cell AJs.